Acute Gastric Volvulus on Hiatal Hernia. (10th December 2020) - KAOUKABI, Abdessamad EL; MENFAA, Mohamed; HASBI, Samir; SAKIT, Fouad; CHOHO, Abdelkrim
Abstract : The gastric volvulus is defined as an abnormal rotation of all or part of the stomach around one of its axes, creating the conditions of an upper abdominal obstruction with gastric dilation and risk of strangulation. It is a rare entity that requires a surgical treatment, and its diagnosis is often delayed due to frequently aspecific symptoms. We will describe the observation of a 62 year old patient who presented to the emergency department for acute epigastric pain with dyspnea. The thoracoabdominal CT has demonstrated a stasis stomach on pyloric obstacle evoking a gastric torsion. An upper gastrointestinal endoscopy (EGD) and an upper gastrointestinal contrast made it possible to diagnose an acute gastric volvulus on hiatal hernia. A midline laparotomy was performed with detorsion of the stomach and repair of the hiatal hernia. The patient recovered gradually and was discharged on the sixth postoperative day. Three months after the operation, the patient remained asymptomatic.